An Italian-Mediterranean Dietary Pattern Developed Based on the EAT-Lancet Reference Diet (EAT-IT): A Nutritional Evaluation - Massimiliano Tucci; Daniela Martini; Cristian Del Bo’; Mirko Marino; Alberto Battezzati; Simona Bertoli; Marisa Porrini; Patrizia Riso (Foods, 2021)
There is an urgent need to promote healthy and sustainable diets that are tailored to the preferences and cultures of different populations. The present study aimed to (i) define a Mediterranean dietary pattern in line with the EAT-Lancet Commission reference diet (ELCRD), based on 2500 kcal/day and adapted to the Italian food habits (EAT-IT); (ii) develop a mid/long-term dietary plan based on EAT-IT and a dietary plan based on the Italian Dietary Guidelines (IDG); (iii) compare the two dietary plans in terms of portions, frequencies of consumption, and nutritional adequacy based on the nutrient and energy recommendations for the Italian adult population. The main differences between the two plans were related to the higher amount of fruit and vegetables in the IDG compared to the EAT-IT, while the EAT-IT plan was higher in nuts and legumes, which represent the main protein sources in the ELCRD. Differences in the protein sources, especially milk and derivatives, and for cereal-based foods, were also found. Dietary plans were comparable for most nutrients, except for higher energy from lipids and vegetal protein, a higher amount of fiber, and lower levels of calcium that were evidenced for the EAT-IT dietary plan compared to the IDG-based one. In conclusion, the analysis of the EAT-IT demonstrated certain nutritional issues. It remains to be determined whether this may represent a health concern in further studies aimed at investigating the feasibility of sustainable dietary patterns.